2011
DOI: 10.1007/s10120-011-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of lymph node metastasis following a curative endoscopic submucosal dissection of an early gastric cancer

Abstract: Currently in Japan, differentiated gastric submucosal invasive cancers \500 lm (SM1) with negative lymphovascular involvement are included in expanded pathological criteria for curative endoscopic treatment. This is based on a retrospective examination of surgical resection cases in which patients suitable for such expanded criteria were determined to have a negligible risk of lymph node metastasis. We performed endoscopic submucosal dissection on a 65-year-old male with early gastric cancer in April 2005, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Oda et al [14] reported a multicenter questionnaire study on long-term outcomes of curative ESD resection for expanded indication in 1,289 patients with EGC. In this study, the percentages of lymph nodes or distant metastasis with more than 5-year follow up was 0.15 % in intramucosal differentiated-type cancers [2 cm in size without ulceration (1/708; 95 % CI, 0.004-0.84 %), 0 % in intramucosal differentiated-type cancers B3 cm in size with ulceration (0/305; 95 % CI, 0-1.26 %), 0 % in intramucosal undifferentiated-type cancer 2 cm in size without ulceration (0/58; 95 % CI, 0-6.38 %), and 1.0 % in SM1 differentiated-type cancers B3 cm in size (2/218; 95 % CI, 0.12-3.55 %: one of the two cases is this case and the other was published by Oya et al [13]). This retrospective study also indicated the slightly higher 95 % CI upper limits in SM1 differentiated-type cancers B3 cm than those in differentiated-type intramucosal gastric cancers, except for the small number of undifferentiated-type intramucosal EGC.…”
Section: Case Reportmentioning
confidence: 68%
See 1 more Smart Citation
“…Oda et al [14] reported a multicenter questionnaire study on long-term outcomes of curative ESD resection for expanded indication in 1,289 patients with EGC. In this study, the percentages of lymph nodes or distant metastasis with more than 5-year follow up was 0.15 % in intramucosal differentiated-type cancers [2 cm in size without ulceration (1/708; 95 % CI, 0.004-0.84 %), 0 % in intramucosal differentiated-type cancers B3 cm in size with ulceration (0/305; 95 % CI, 0-1.26 %), 0 % in intramucosal undifferentiated-type cancer 2 cm in size without ulceration (0/58; 95 % CI, 0-6.38 %), and 1.0 % in SM1 differentiated-type cancers B3 cm in size (2/218; 95 % CI, 0.12-3.55 %: one of the two cases is this case and the other was published by Oya et al [13]). This retrospective study also indicated the slightly higher 95 % CI upper limits in SM1 differentiated-type cancers B3 cm than those in differentiated-type intramucosal gastric cancers, except for the small number of undifferentiated-type intramucosal EGC.…”
Section: Case Reportmentioning
confidence: 68%
“…Oya et al [13] reported another case of regional lymph node metastasis 49 months after ESD in a patient with SM1 gastric cancer that fulfilled the expanded criteria. The patient's ESD was actually a noncurative resection based on the current version of the treatment guidelines because of a poorly differentiated component with ulceration [3].…”
Section: Case Reportmentioning
confidence: 99%
“…In addition, local recurrence and regional or distant LN metastasis remain critical issues. In this study, two patients in whom curative ESD was achieved for SM1 [19,20]. Therefore, more careful attention must be paid, in particular, to patients with SM1 invasive EGC lesions for which curative ESD has been achieved.…”
Section: Discussionmentioning
confidence: 94%
“…The primary lesions in the two patients were SM1 invasive cancers. The patient who developed regional LN metastasis underwent salvage surgery, and no [19]. The other patient who developed distant LN metastasis with local recurrence received systemic chemotherapy but died of gastric cancer about 2 years after recurrence [20].…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…A number of studies have reported a favorable prognosis after curative resection of EGC by endoscopic resection [5][6][7][8]. Although the 5-year overall survival and 5-year disease-specific survival rates of patients with EGC after curative therapy are more than 97% and 99% respectively [7][8][9], there have been several reports of EGC recurrence after curative treatment, which can lead to unfavorable outcomes [8,10,11]. After curative endoscopic resection, the recurrence rate ranges from 4.5% to 16%.…”
Section: Introductionmentioning
confidence: 99%